Tadashi Kawamata, Kōichi Kurita, Motoi Yamamoto : des matériaux naturels comme indices de la précarité des liens sociaux - Nicolas-Xavier Ferrand (Images Re-Vues)
This paper aims to analyse the way three Japanese contemporary artists, namely Tadashi Kawamata, Kōichi Kurita and Motoi Yamamoto, employ fragile organic materials (wood, soil, salt), in formal propositions that question social links between humans and non-humans. These works are motivated by a precarious and ephemeral perception of existence: relatives’ passings, soil’s destruction, nuclear and climatic catastrophes, systematic urban reorganization. The material, always collected somewhere specific, is then less a symbolic and visual operation of nature’s aestheticization than an actualization of a certain social structure where humans and non-humans live together. The analysis of agency’s distribution allows to better situate those works into Philippe Descola’s « ontologies », such as « animism » and « analogism », and to differenciate them from similar Western practices activating a « natularist » scheme: the artist always undergoes the agency of a place, a material, a non-human, as him and viewers are stuck into a relationship network where the frontiers between nature and culture aren’t operating.